2018
DOI: 10.1007/s40256-017-0262-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Prostacyclin Pathway with Selexipag in Patients with Pulmonary Arterial Hypertension Receiving Double Combination Therapy: Insights from the Randomized Controlled GRIPHON Study

Abstract: BackgroundIn pulmonary arterial hypertension (PAH), combination therapy is an important treatment strategy. Although randomized controlled trial data are available to support the combination of two therapies, data regarding triple combination therapy are few.ObjectiveThe phase III GRIPHON trial enrolled 1156 patients with PAH, including 376 receiving background double combination therapy. We evaluated the efficacy and safety of selexipag as a third agent in these patients and further analyzed this subgroup acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 11 publications
3
74
1
8
Order By: Relevance
“…92,93 More recently, the SERAPHIN and the long-term GRIPHON trials demonstrated lower morbidity and mortality rates with the addition of macitentan and selexipag on a background therapy, respectively. 94,95 General Measures…”
Section: Combination Therapy Versus Initial Monotherapymentioning
confidence: 99%
“…92,93 More recently, the SERAPHIN and the long-term GRIPHON trials demonstrated lower morbidity and mortality rates with the addition of macitentan and selexipag on a background therapy, respectively. 94,95 General Measures…”
Section: Combination Therapy Versus Initial Monotherapymentioning
confidence: 99%
“…В исследование GRIPHON были включены 1156 пациентов с ЛАГ, в т. ч. n=376, исходно получавших двойную комбинированную терапию. У пациентов, получавших двойную пероральную комбинированную терапию, селексипаг на 37% уменьшал риск достижения первичной комбинированной конечной точки по сравнению с плацебо (ОР 0,63; 95% ДИ: 0,44-0,90) (рисунок 2) [10]. При анализе в подгруппах с различной исходной тяжестью симптомов в группе селексипага показано снижение риска на 64% по сравнению с плацебо (ОР 0,36; 95% ДИ 0,14-0,91) у пациентов с ФК II по ВОЗ и на 26% (ОР 0,74; 95% ДИ: 0,50-1,10) у пациентов с ФК III по ВОЗ (рисунок 3).…”
Section: препарат нового поколения для лечения лагunclassified
“…составила у пациентов с симптомами ФК II по ВОЗ в группе терапии селексипагом 93,3% (80,6-97,8) и 79,3% (65,7-88,0) в группе плацебо, а также 79,5% (70,2-86,1) и 70,1% (61,1-77,4) у пациентов с симптомами ФК III по ВОЗ в группе терапии селексипагом и плацебо, соответственно. Лечение селексипагом сопровождалось снижением риска смерти вследствие ЛАГ или госпитализации по поводу ухудшения ЛАГ на 39% по сравнению с плацебо (ОР 0,61; 95% ДИ: 0,39-0,96), что соответ-ствовало результатам в общей популяции исследования GRIPHON [9,10]. Эти результаты свидетельствуют о том, что относительное снижение риска прогрессирования заболевания и смерти на фоне терапии селексипагом по сравнению с плацебо может быть более выраженным у пациентов с ФК II по ВОЗ, что согласуется с данными предшествующего исследования при ЛАГ [11].…”
Section: препарат нового поколения для лечения лагunclassified
See 1 more Smart Citation
“…Selexipag, a prostacyclin receptor agonist, is an orally available prodrug which has shown significantly improvements in the treatment of pulmonary arterial hypertension in adults . Thus, selexipag may have a future potential in the treatment of PPHN .…”
Section: Therapy Of Pphnmentioning
confidence: 99%